Adult Learning Processes in Non-Formal Education Contexts - Acero Pereira, Celia (Pontificia Universidad Javeriana, 2018)
It is necessary to evaluate the learning context and individual characteristics of learners to understand the adult learning process. In this study, adult learning processes at non-formal situations according to Kolb´s model (1984) are described, considering its variability according to individual characteristics. Variability in adult learning processes was found, with socio-laboral conditions and risk trajectories playing a relevant role. These results are discussed, and methodological implications for planning adult learning experiences are highlighted.